Reduction of animal suffering in rabies vaccine potency testing by introduction of humane endpoints. (March 2017) - Takayama-Ito, Mutsuyo; Lim, Chang-Kweng; Nakamichi, Kazuo; Kakiuchi, Satsuki; Horiya, Madoka; Posadas-Herrera, Guillermo; Kurane, Ichiro; Saijo, Masayuki
Abstract: Potency controls of inactivated rabies vaccines for human use are confirmed by the National Institutes of Health challenge test in which lethal infection with severe neurological symptoms should be observed in approximately half of the mice inoculated with the rabies virus. Weight loss, decreased body temperature, and the presence of rabies-associated neurological signs have been proposed as humane endpoints. The potential for reduction of animal suffering by introducing humane endpoints in the potency test for inactivated rabies vaccine for human use was investigated. The clinical signs were scored and body weight was monitored. The average times to death following inoculation were 10.49 and 10.99 days post-inoculation (dpi) by the potency and challenge control tests, respectively, whereas the average times to showing Score-2 signs (paralysis, trembling, and coma) were 6.26 and 6.55 dpi, respectively. Body weight loss of more than 15% appeared at 5.82 and 6.42 dpi. The data provided here support the introduction of obvious neuronal signs combined with a body weight loss of ≥15% as a humane endpoint to reduce the time of animal suffering by approximately 4 days.